Diseño de un dispositivo para simular las condiciones de ensayo de retención de los vidrios panorámicos según la norma FMVSS 212 para Cesvi Colombia (2019)
In order to elaborate this project, we began to investigate about the existing international regulations for the analysis of the retention of the panoramic glasses during collision conditions; Likewise, through the regulations obtained, the evaluation of the current systems was developed to carry out these simulations, determining the conditions in which they were carried out. In a joint way, the impact process was conceptualized in which the different collision types for these tests were analyzed, allowing to determine the set of forces, reactions and conditions experienced during the test; At the same time, different alternatives were evaluated regarding the probable location of the device; After this the parameters for the device were defined, starting the detailed design of the elements that compose it.